Sosialisasi Adab Pendidik Dan Peserta Didik Serta Relevansinya Terhadap Pendidikan Islam Di MAN 2 Langkat - Fatimah Ahmad; Maulida (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
The progress and development of technology that accompanies education to day has a positve impact on educators and students in the form of ease of learning information and communication facilities, but has a negative impact in the form of the collapse of character. Ethicts, morals, manners and manners as we often see on social media online or offline.the moral crisis that we see today is that the low level of honoring and respecting educators can be seen as aform of immorality for people who seek knowledge without bringing benefits and blessings to themselves and the environmant around them. This education aims to determine the etiquette of educators and students regarding the relevance of the Islamic Religous perspective. This type of resesearch, namely descriptive in nature. Disscussion related to the etiquette of educators and studnt, the relevance of Islamic education to the resesearer of adab and its relationship pattens with interaction and comuunication between educators and students and their education ideally according to Islamic teachings based on the arguments of the quran an d hadits.